THE ROLE OF N-DOPING TO THE PORE CHARACTERISTICS OF ACTIVATED CARBON FROM VETIVER ROOT DISTILLATION WASTE - Yohana Fransiska Ferawati; Ratna Frida Susanti (Metalurgi, 2021)
This work studied the effect of nitrogen functional group modification on activated carbon synthesized from vetiver root waste on pores development. Synthesis of activated carbon was carried out by hydrothermal carbonization of vetiver root waste at a temperature of 225 ⁰C for 18 hours followed by chemical activation using K2FeO4as activated agent in a furnace at temperature of 800 ⁰C for 2 hours with nitrogen atmosphere flowed at a rate of 100 mL/minute. Urea was used as a nitrogen source. The variation of urea concentration was 1:0 (AC0–800), 1:3 (AC3–800) and 1:5 (AC5–800). The results showed that these activated carbons have mesoporous characteristics with the largest Brunauer Emmett Teller (SBET) surface area of 552.90 m2g-1 and average pore width 3,43 nm. The presence of nitrogen functional group was observed in the Fourier Transform Infrared Spectrometer analysis. Synthesis of activated carbon from vetiver root waste with an addition of urea is the newest method to produce mesoporous activated carbon for electrode and  support catalyst purposes.